Economic sectors and globalization channels to gender economic inclusion in Sub-Saharan Africa - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2023)
This study complements the extant literature by assessing economic sector and globalization channels for gender economic inclusion. The study is focused on 35 countries in sub-Saharan Africa for the period 1995-2019 and the empirical evidence is based on fixed effects regressions. The following findings are established. First, economic and political globalization positively affect female employment in agriculture and the positive effect of economic globalization is driven by the trade globalization dynamic while social globalization negatively affects female employment in agriculture and the negative effect of social globalization is driven by cultural and informational globalization dynamics. Second, aggregate globalization and sub-components (i.e. economic globalization, social globalization and political globalization) negatively affect gender employment in the industry and the negative effect is driven by the financial globalization sub-component of economic globalization and by the informational and cultural components of social globalization. Third, aggregate globalization and sub-components positively affect gender employment in the service sector and the corresponding positive effect is driven by the trade globalization sub-component of economic globalization and by all sub-components (i.e. interpersonal, informational and cultural dimensions) of social globalization. In the terms of policy implications, policy makers should focus on promoting dimensions of globalization that are established to positively influence female employment as well as put in place measures that are designed to reverse the negative incidence of globalization dynamics that have been established to affect female employment. Moreover, policy makers should also be aware of the fact that when formulating the corresponding policies, the effect of globalization is contingent on globalization dynamics as well as on various economic sectors.
Keywords: E60; F40; F59; D60; O55; 330; Globalization; female; gender; labour force participation; sub-Saharan Africa